Edukasi Pemeriksaan dan Hasil Pemeriksaan Papsmears dalam Upaya Pencegahan Ca Cervix - Devi Permatasari (Universitas Muhammadiyah Klaten, 2026)
Cervical cancer is one of the leading causes of cancer death in women in Indonesia, with a high incidence rate, especially in Central Java Province. The low awareness and participation of women of childbearing age in early detection, such as Pap smears and VIA examinations, are important factors in the increase in cases of advanced cervical cancer. This community service aims to increase women's understanding and awareness of the importance of early detection of cervical cancer through education and Pap smear examinations. Education is carried out by providing information on risk factors, the benefits of routine examinations, and the Pap smear procedure which is simple, safe, and covered by BPJS. The results of the activity showed an increase in knowledge and positive attitudes towards the importance of early detection of cervical cancer. This effort is expected to encourage women of childbearing age to undergo regular examinations so that the incidence and death rate from cervical cancer can be reduced. The objectives of this community service are Specific Objectives: to increase women's knowledge about the importance of Pap smear examinations, form a positive attitude towards cervical cancer prevention, and encourage women's participation in early detection of cervical cancer. Community service results Most respondents (88.2%) showed negative Pap smear results, indicating a healthy cervix after education on early detection of cervical cancer. As many as 11.8% of respondents experienced atrophic smears, which are cell changes due to decreased estrogen in postmenopausal women, which are not a sign of malignancy but require further monitoring if clinical symptoms occur.